The Speech Act Used By English Lecturer And Students in Blended Learning During New Normal Life - Berliana R Br Naipospos; Sulasmi Sulasmi; Herawati Br Bukit (Program Studi Pendidikan Biologi, 2022)
The transmission of COVID 19 has actually increased and become new cluster, namely Omicron has forced all sectors to demonstrate innovation including Education world, and one of the innovations is Blended Learning. Language as communication tool must be understood by speaker and interlocutor so that it doesn’t cause misunderstanding. If interlocutor and speaker both understand the meaning of speech conveyed, then information conveyed by speaker to interlocutor can work well. Phonetic understanding is not only literal meaning, but also implicit meaning. The study reasons are, firstly, it is concerned with classroom interaction analysis focusing on spoken language utilizing Pragmatic linguistic analysis about speech act used. Secondly, the classification and types of speech act, so it will find the speech act differences between online and face-to-face. This research was descriptive qualitative design by observing and recording conversations between English lecturers and pharmacy students during blended learning during new normal life as data collection techniques. Research results found the utterances in English lecturer and pharmacy students’ conversations are dominated by illocutionary act, which is as much as 65%. It showed that most of the speeches, both spoken by lecturers and students, are speeches that contain other meanings. The second rank was locutionary acts (20%). Finally, it is known that perlocutionary acts are the speech acts that appear the least, which is only 15% of all conversations. There are five illocutionary categories in face to face learning, namely assertive, directive, expressive, commissive, and declarative, while there is no declarative in online learning. It is known that in blended learning, the dominant classification of speech act used by English lecturer was directive which consist 32 lecturer's utterances as many as 54%. Whereas representative as dominant classification of speech act used by pharmacy students which consist 30 students’ utterances as many as 55%